The patent innovation ecosystem of China’s ready-to-cook foods industry: spatiotemporal evolution, technical clustering, and collaborative network analysis - Cai, Jingwen; Hu, Haoqian; Yin, Yifen; Yu, Yuanyuan; Wang, Chunning (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe ready-to-cook (RTC) foods sector represents a rapidly growing industry where innovation patterns and technological evolution are pivotal for sustainable development. This study establishes a comprehensive “space-time-technology-network” analytical framework to systematically investigate China’s RTC patent innovation ecosystem.MethodsWe analyzed 1,180 patent records through an integrated approach combining time-series analysis, spatial distribution mapping, technology classification, and social network analysis to reveal multidimensional characteristics of RTC innovation.ResultsOur analysis identified three distinct evolutionary phases in RTC patents: an embryonic stage (2018–2021), a boom period (2022–2023), and a current adjustment phase (2024). Innovation activities demonstrated marked regional concentration, forming three primary clusters: the Pearl River Delta, Yangtze River Delta-Shandong, and Fujian-Hunan regions. Technologically, the sector is dominated by food processing & forming technology and packaging technology, which have evolved into a highly interconnected “small world” network structure. While enterprises constitute the primary innovation drivers (76.54%), the collaboration network remains notably fragmented. Knowledge flows occur primarily through three channels: intra-corporate group collaborations, industry-university-research partnerships, and regional industrial clusters.DiscussionThe RTC patent ecosystem exhibits four defining characteristics: explosive growth, regional agglomeration, multi-technology convergence, and fragmented collaboration networks. This study provides both a theoretical framework and empirical basis for understanding innovation dynamics of emerging food industries and offers valuable insights for promoting high-quality development in the RTC foods sector.